The potential of new media on film poster in Malaysia / Muhammad Ashraf Omar - Omar, Muhammad Ashraf (2014)
New media refers to on-demand access to content anytime, anywhere, on any digital device, as well as interactive user feedback, and creative participation. Another aspect of new media is the real-time generation of new and unregulated content. Most technologies described as "new media" are digital, often having characteristics of being manipulated, networkable, dense, compressible, and interactive. Some examples may be the Internet, websites, computer multimedia, video games, augmented reality, CD-ROMS, and DVDs. New media does not include television programs (only analog broadcast), feature films, magazines, books, or paper-based publications - unless they contain technologies that enable digital interactivity. Movie posters are promotional items created by film studios to advertise feature films. The theaters currently screening the movie use oversized posters on outside marquees to attract customers, while smaller posters are placed outside each showing room. After the commercial run of the movie is over, movie posters are often reproduced for consumers and the originals become highly collectible.